Inovasi Pelaksanaan Program Pendidikan Karakter, Tahfizh dan Kuliah Motivasi Pendekar Takesi di SMA Negeri 4 Padang - Abdulimei Hidayat; Afnibar Afnibar; Muhammad Zalnur (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2025)
Character education is a fundamental aspect in shaping the character and civilization of a dignified nation, as mandated by the Indonesian National Education System Law (SISDIKNAS) No. 20 of 2003. However, reality shows the existence of a moral crisis among adolescents, exacerbated by the negative impacts of technological and informational developments. In response to this challenge, SMA Negeri 4 Padang has implemented an innovative character education program based on tahfizh and motivational lectures, known as “Pendekar Takesi.” This program, which has been running since 2018, aims to develop students’ spiritual, moral, and academic potential, as well as strengthen their religious identity.This study aims to analyze in depth the planning, implementation, and evaluation of the “Pendekar Takesi” program at SMA Negeri 4 Padang. Using a descriptive qualitative approach, data were collected through observations, interviews with the principal, vice principal for curriculum, program coordinators, and students, as well as documentation studies. Data validity was ensured through methodological and source triangulation. The findings indicate that the “Pendekar Takesi” program is well-planned, involving all school stakeholders, and designed to integrate the character values of the Profil Pelajar Pancasila (Pancasila Student Profile). Its implementation includes weekly tahfizh Al-Qur’an activities in class and monthly or semester-based motivational lectures in the school hall, facilitated by teachers and guest speakers. Program evaluation is conducted periodically at the end of each semester, with outcomes contributing to students’ Islamic Education grades. Although the program has succeeded in enhancing students’ tahfizh abilities and learning motivation, challenges remain, including funding, the availability of qualified tahfizh teachers, and limited student interest. Solutions implemented include optimizing school funds, empowering students as peer mentors, and providing continuous motivation. The “Pendekar Takesi” program has proven effective in fostering students who are faithful, intelligent, and high-achieving, making it a relevant model for replication in other schools with local contextual adjustments.